Psychological Characteristics Of High School Women's Futsal Athletes In Bengkulu - Puput Eka Novianti; Syahrastani Syahrastani; Nugroho Susanto; Zulbahri Zulbahri (JETL (Journal of Education, Teaching and Learning), 2025)
This research was conducted on the basis of a lack of knowledge about the psychological characteristics of high school female futsal athletes in Bengkulu City. This study aims to determine the Psychological Characteristics of High School Female Futsal Athletes in Bengkulu City. This type of research is descriptive research with survey method.  The subjects of this study were all athletes who were active in the high school women's futsal club in Bengkulu City consisted of 3 schools namely SMAN 1 Bengkulu City, SMAN 6 Bengkulu City and SMAS Muhammadiyah 4 Bengkulu City which amounted to 57 athletes. Instruments and data collection techniques used in this study were questionnaires and interviews. The data analysis technique used was descriptive analysis with percentages. The results stated that the percentage of questionnaires in general was 56% good, the motivation aspect questionnaire was 65% very good, the self-confidence aspect questionnaire was 44% good, the anxiety control aspect questionnaire was 42% quite good, the mental preparation aspect questionnaire was 35% good, the teamwork aspect questionnaire was 46% very good, the concentration aspect questionnaire was 37% quite good and the interview was generally 54% good. It can be concluded that, aspects of the psychological characteristics of high school female futsal athletes in Bengkulu City that need to be improved and improved are aspects of anxiety control and concentration